1998
DOI: 10.1044/jslhr.4103.627
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent and Predictive Validity of an Early Language Screening Program

Abstract: The efficacy of screening 2-year-old children for language delay using a parent-report questionnaire was investigated in three studies. The Language Development Survey (Rescorla, 1989) was mailed to 650 families at the time of their child's second birthday. Fifty-three percent of the surveys received by parents were completed and returned. Screening outcomes were then compared, in double-blind fashion, with the results of comprehensive clinical evaluations at ages 2 (N = 64) and 3 (N = 36). Parents' report of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 27 publications
5
76
0
3
Order By: Relevance
“…Eleven studies from 10 publications used instruments that take Յ10 minutes to administer for children up to 2 years old, including the Early Language Milestone Scale, 30,55 Parent Evaluation of Developmental Status, 56 Denver Developmental Screening Test II (language component), 57 Pediatric Language Acquisition Screening Tool for Early Referral, 52 Clinical Linguistic and Auditory Milestone Scale, 58 Language Development Survey, [59][60][61] Development Profile II, 57 and the Bayley Infant Neurodevelopmental Screener 62 (Table 4). Of these studies, 6 tested expressive and/or receptive language, 30,52,55,57,62 3 tested expressive vocabulary, 59-61 1 tested expressive language and articulation, 56 and 1 tested syntax and pragmatics.…”
Section: Ages 0 To 2 Yearsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven studies from 10 publications used instruments that take Յ10 minutes to administer for children up to 2 years old, including the Early Language Milestone Scale, 30,55 Parent Evaluation of Developmental Status, 56 Denver Developmental Screening Test II (language component), 57 Pediatric Language Acquisition Screening Tool for Early Referral, 52 Clinical Linguistic and Auditory Milestone Scale, 58 Language Development Survey, [59][60][61] Development Profile II, 57 and the Bayley Infant Neurodevelopmental Screener 62 (Table 4). Of these studies, 6 tested expressive and/or receptive language, 30,52,55,57,62 3 tested expressive vocabulary, 59-61 1 tested expressive language and articulation, 56 and 1 tested syntax and pragmatics.…”
Section: Ages 0 To 2 Yearsmentioning
confidence: 99%
“…58 For the 10 fair-and good-quality studies that provided data to determine sensitivity and specificity, sensitivity ranged from 22% to 97% and specificity ranged from 66% to 97%. 30,52,[56][57][58][59][60][61][62] Four studies reported sensitivity and specificity of Ն80% when using the Early Language Milestone Scale, 30 the Language Development Survey, 59,60 and the Clinical Linguistic and Auditory Milestone Scale. 58 The study of the Clinical Linguistic and Auditory Milestone Scale also determined sensitivity and specificity by age and reported higher sensitivity/ specificity at 14 to 24 months of age (83%/93%) than 25 to 36 months of age (68%/89%) for receptive function but lower sensitivity/specificity at 14 to 24 months of age (50%/91%) than 25 to 36 months of age (88%/98%) for expressive function.…”
Section: Ages 0 To 2 Yearsmentioning
confidence: 99%
“…[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] (Supplemental Table 3). Supplemental Table 4 describes relevant screening instruments.…”
Section: Figurementioning
confidence: 99%
“…32,33,42,43 Both studies examined the accuracy of the screener at 2 years in relation to the reference standard (a diagnostic tool) at both 2 years and 3 years. In the LDS study, 43 sensitivity for detecting a language delay at 3 years was 67% (91% at 2 years).…”
Section: Accuracy Of Longer-term Predictionmentioning
confidence: 99%
“…Παρουσιάζει ε̟ίσης ισχυρή συγχρονική και ̟ροβλε̟τική εγκυρότητα (Klee et al, 1998· Rescorla & Alley, 2001· Rescorla, Ratner, Jusczyk & Jusczyk, 2005 ενώ, α̟' όσο γνωρίζουµε, είναι το µόνο σχετικό εργαλείο ̟ου έχει σταθµιστεί και σε ελληνικό ̟ληθυσµό (Ν= 274) (Ερωτηµατολόγιο Γλωσσικής Ανά̟τυξης -ΕΓΑ, στο: ΣΑΕΒΑ, Τσαούσης, 2009).…”
unclassified